2021
DOI: 10.3389/fimmu.2021.701275
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Peptide Designed to Neutralize Lipopolysaccharides Attenuates Metaflammation and Diet-Induced Metabolic Derangements in Mice

Abstract: Metabolic endotoxemia has been suggested to play a role in the pathophysiology of metaflammation, insulin-resistance and ultimately type-2 diabetes mellitus (T2DM). The role of endogenous antimicrobial peptides (AMPs), such as the cathelicidin LL-37, in T2DM is unknown. We report here for the first time that patients with T2DM compared to healthy volunteers have elevated plasma levels of LL-37. In a reverse-translational approach, we have investigated the effects of the AMP, peptide 19-2.5, in a murine model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…We also examined the mRNA expression level of cramp , which is a unique antimicrobial peptide in the gut produced by colonic epithelial cells and playing an important role in regulating gut microbes ( 52 , 53 ). Mohammad et al found that cramp was significantly higher in patients with T2DM than in healthy subjects and it could regulate lipid accumulation in adipocytes and hepatocytes ( 54 ). In our present study, cramp was elevated in the HFD group, suggesting the attempt to re-establish the disturbed barrier.…”
Section: Discussionmentioning
confidence: 99%
“…We also examined the mRNA expression level of cramp , which is a unique antimicrobial peptide in the gut produced by colonic epithelial cells and playing an important role in regulating gut microbes ( 52 , 53 ). Mohammad et al found that cramp was significantly higher in patients with T2DM than in healthy subjects and it could regulate lipid accumulation in adipocytes and hepatocytes ( 54 ). In our present study, cramp was elevated in the HFD group, suggesting the attempt to re-establish the disturbed barrier.…”
Section: Discussionmentioning
confidence: 99%
“…This model emphasises the significance of co‐receptor activity in initiating TLR4‐TLR6 signalling and activating inflammatory pathways, which increases IL‐6, TNF‐α and other inflammatory markers (Stewart, Stuart, et al, 2010). Further, CD36 has been implicated in the association between obesity and metaflammation (the metabolic inflammation accompanying metabolic diseases) (Mohammad et al, 2021). Its increased expression and activity in individuals with obesity may contribute to the development of metaflammation and associated metabolic complications (Caputo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The free NF-κB becomes activated and enters the nucleus to regulate the transcription of immune-related receptors, cytokines, adhesion molecules, and other target genes, causing tissue damage ( Fattori et al, 2017 ). It is well documented that NF-κB is essential in regulating inflammatory signaling pathways in the liver and inhibition of NF- κB reduces the extent of liver injury ( Mohammad et al, 2021 ). In our study, we found that the levels of p-NF-κB/NF-κB and p-IKK/IKK were increased in OA-stimulated HepG2 cells, which were attenuated by Foxa2 overexpression.…”
Section: Discussionmentioning
confidence: 99%